The Effectiveness of Using Digital Posters Presentation to Enhance Students’ Speaking Skill - Sarah Nurazizah; Ila Amalia; Tri Ilma Septiana (LPPM Universitas Bina Sarana Informatika, 2023)
This study aimed to investigate the effectiveness of digital poster presentations to enhance students' speaking skills. in this study, there are three researcher questions, namely: (1) How was the speaking skill of the eighth grade students of SMP Islam Ar-Rochmah Cilegon before using a digital poster presentation? (2) How is the Implementation of Using Digital Poster Presentation to Enhance Students' Speaking Skill? (3) How is the effectiveness of Digital Poster Presentation to enhance students’ speaking skill on descriptive text?. This study used a quasi-experimental study that involved two classes, namely VIII A which acted as a control class, and VIII B which acts as an experimental class consisting of 33 students in each class so the total number of students is 66 students of class VIII as respondents. The final finding of this study revealed that t0 is greater than the t table at a significant level of 5%, namely t table = 0.886 and t observation = 4.32. In addition, the results of observations show that students are more motivated in learning English, especially in speaking subjects. Based on the above results, it can be concluded that digital poster presentation can improve students' speaking ability compared to those who do not use it